Identification of risk factors for postpartum urinary retention following vaginal deliveries: A retrospective case-control study. (December 2019) - Lamblin, Géry; Chene, Gautier; Aeberli, Camille; Soare, Roxana; Moret, Stéphanie; Bouvet, Lionel; Doret-Dion, Muriel
Abstract: Objective: Postpartum urinary retention (PUR) is an uncommon complication of vaginal delivery, defined as a failure to void spontaneously in the six hours following vaginal birth. The objective of this study was to identify risk factors for PUR in order to provide prompt management. Study Design: A retrospective, comparative, case-control study, including two groups of 96 patients who delivered vaginally, was conducted at the Women and Children's University Hospital in Lyon, France. Patients were selected based on data extraction from the medical records of the obstetrics and gynecology department. The first group included patients with postpartum urinary retention and the second group, without PUR, was selected randomly, respecting 1:1 matching criteria, paired according to the year of delivery and patient's age at delivery. Results: Logistic regression analysis found that instrumental delivery (OR 13.42, 95%CI [3.34;53.86], p = 0.0002), absence of spontaneous voiding before leaving the delivery room (OR 6.14, 95%CI [2.56;14.73], p < 0.0001), no intact perineum (OR 3.29, 95%CI [1.10;9.90], p = 0.03) and vulvar edema or perineal hematoma (OR 8.05, 95%CI [1.59;40.67], p = 0.01) were independent risk factors associated with PUR. Conclusion: The present study identified risk factors for PUR that should be taken into consideration as soon as delivery is over in order to implement appropriate management. Future studies are needed to assess the contribution of early systematic bladder scanning in patients with risk factors for early diagnosis of PUR.